The effect of alkali metal ions on the electronic structure of p-anisic acid 1. Issue 5 (2010) - Kalinowska, M.; Świsłocka, R.; Regulska, E.; Lewandowski, W.
Abstract : FT-IR (in solid state and solution), FT-Raman, UV and 1 H, 13 C NMR spectra of p-methoxybenzoic ( p -anisic) acid and lithium, sodium, potassium, rubidium and caesium p -methoxybenzoates ( p -anisates) were registered, assigned and analyzed. The structures of anisic acid and Li, Na and K p -anisates were optimised at the B3LYP/6-311++G** level. The IR spectra and NPA, ChelpG and MK atomic charges were calculated. The effect of metal ions on the electronic charge distribution in ligand was discussed.